Visual Communication of The Edit Room Community's Odos Poster As A Media For Da'wah - Darma Yana Sara; Kamaluddin Tajibu; Haidir Fitra Siagian (Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Da’wah has evolved beyond traditional lectures, utilizing visual communication design media such as posters. Through its ODOS program, the Room Edit community plays a significant role in disseminating Islamic messages widely through the Telegram platform. This study aims to analyze ODOS posters as a medium of da’wah and identify the messages contained within them. The method used is qualitative descriptive analysis with Ferdinand de Saussure’s semiotic analysis, distinguishing between signifier (the sign) and signified (the meaning). The study results indicate that ODOS posters have visual elements that complement each other, effectively capturing attention and providing clear context for the meaning of the da’wah message. Visual elements not only serve as decoration but also as a communication medium that reinforces the intended meaning. The content of the da’wah messages in ODOS posters includes creed, ethics, and sharia. Creed messages emphasize belief in Allah’s decrees, while ethical messages focus on gratitude, patience, and moral guidance. Sharia messages highlight the importance of prayer as the first act to be accounted for. From the analysis, it is evident that moral messages are more dominant, reflecting the daily behavior of Muslims, which is a direct reflection of their faith.